-4/1×7/3-(-4) ×9/10 simplify
Answers
Answered by
0
Answer:
yu can leave your answer at 21/10 and if it is asking for the simplest form yu should write 2.1
Step-by-step explanation:
and plz mark my answer the brainliast answer
Attachments:
![](https://hi-static.z-dn.net/files/d87/f008ce02b625d758c586cb23de5195ff.jpg)
Answered by
0
Answer:
-4/1÷7/3-(-4)×9/19
= -28/3-(-4)×9/10
= -28/3+4×9/10
= (-28+12/3)×(9/10)
= -40/3×9/10
= -49/30: Ans
.
.
.
.
hope it helps you
Similar questions
English,
5 months ago
English,
5 months ago
India Languages,
5 months ago
Math,
11 months ago
Math,
11 months ago